A narrative review of schemas and schema therapy outcomes in the eating disorders. (July 2015) - Pugh, Matthew
Abstract: Whilst cognitive-behavioural therapy has demonstrated efficacy in the treatment of eating disorders, therapy outcomes and current conceptualizations still remain inadequate. In light of these shortcomings there has been growing interest in the utility of schema therapy applied to eating pathology. The present article first provides a narrative review of empirical literature exploring schemas and schema processes in eating disorders. Secondly, it critically evaluates outcome studies assessing schema therapy applied to eating disorders. Current evidence lends support to schema-focused conceptualizations of eating pathology and confirms that eating disorders are characterised by pronounced maladaptive schemas. Treatment outcomes also indicate that schema therapy, the schema-mode approach, and associated techniques are promising interventions for complex eating disorders. Implications for clinical practice and future directions for research are discussed. Highlights: Eating disorders are associated with pronounced maladaptive schemas across diagnoses. Schemas interact with eating pathology, although how they do so in anorexia nervosa is unclear. Schema-focused models of eating pathology are broadly supported by current research. Schema therapy and schema mode therapy are promising treatments for complex eating disorders.